Responsiveness of Local Governance Anticipating Industrialization Impact on The Environment in Subang Regency - Juana, Tedi; Suparman, Nanang; Sakti, Fadjar Tri (Jurnal Magister Administrasi Publik, 2021)
Subang Regency is one of the strategic places in West Java, Indonesia was projected as an industrial area around 11.250 Ha, which will potentially cause environmental damage. Assuredly Subang Regency’s Government as the leading sector that closes to the industrial estate project should respond to the environmental damage issue properly and responsively. This study analyzes the characteristic of stakeholders' behavior to facing and preventing industrial impact in the period 2020-2021 based on several regulations. Therefore, this research aims to describe the responsiveness of the stakeholders to facing environmental issues caused by the construction of the industrial estate, which was analyzed using the responsiveness theory by (Ansoff et al., 2019). This research used a descriptive method with a qualitative approach. The data were collected for 4 months using purposive sampling with observation, interview, and literature and analyzed by (Milles et al., 2014) technic including data reduction, display data, and drawing conclusions or verification during collecting data and after collecting data. The study showed that Subang Regency’s Government as the leading sector has a good competence in the human resources but needs to develop in the organizational climate and capacity to collaborate and innovate so that the environmental damage issue can be maintained and resolved properly